Analysis of the results of surface free energy measurement of Ti6Al4V by different methods - Schuster, Jonathan Maximiliano (2015)
Surface Free Energy (SFE) of solids should be calculated using theoretical models. The contact angle (CA) measurement on a surface is considered the most practical way to obtain the SFE. The results of five methods based in the models are compared: the method of Zisman (ZI), the geometric mean (GM), the harmonic mean (HM), the Lifshitz-van der Waals / Acid-Base (LW/AB) and the equation of state (ES). The SFE calculated with GM, HM and LW/AB methods change with the amount and type of liquid used, however, when water, glycerol and dimethyl sulfoxide are used together the SFE and its dispersive and polar components are similar in value for the three methods. In the case of the ES model the values of SFE change with the liquid used; finally using the ZI method the SFE values are 20% lower than the values of SFE obtained with the other methods.